A guide to writing a review article for novice researchers - Saputra, Heru; Saputra, Bayu; Ginting, Donny Adiatmana (American Journal of STEM Education, 2024)
Review articles constitute a significant staple of literature liked and sought after by readers and journals. They are vital in capturing key details of recent research endeavors and establishing connections with previous studies on a similar topic. In an era of an increasing number of scientific publications, producing review articles timely is of great importance. This writing delves into the subject matter of the process and elucidates both the methodology and the rationale behind drafting a review article. A brief overview of the review article is introduced. The fundamental rules for writing a review article and its structure are discussed. The importance of good writing is also highlighted. Additionally, the authors present insights into where to publish prepared review papers.